Iowa Birdline update, May 28-June 9, 1997 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Freemyer, Zelbertet al (1997)
Iowa Birdline updates for May 28-June 9, 1997. Highlights of the multiple updates include sightings of a Lazuli Bunting, Black-billed Magpies, a Pacific Loon, and numerous species of Warblers. Also of note were sightings of Barn Owls, a Vermillion Flycatcher, and a Spotted Towhee. Epson - sheet feed/flatbed